VIDEO CERITA ANAK BERBASIS TEKNIK VENTRILOQUIST UNTUK MENINGKATKAN KETERAMPILAN MENYIMAK SISWA KELAS II SEKOLAH DASAR - Alfa Salsabila Sari; Dwi Agus Setiawan; Denna Delawanti Chrisyarani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to develop a learning media in the form of a children's story video based on ventriloquist techniques and to test its feasibility, practicality, and effectiveness in improving the listening skills of second-grade elementary school students. The background of this study is the low listening skills of students and the lack of use of digital learning media. The media developed is a children's story video entitled